IMPLEMENTASI KEBIJAKAN PENANGANAN COVID 19 DI DESA SEA TUMPENGAN KECAMATAN PINELENG KABUPATEN MINAHASA - WALEAN, MARIO; LENGKONG, FLORENCE DAICY; LONDA, VERY (Sam Ratulangi University, 2020)
The purpose of this study was to find out the implementation of the policy on handling Covid 19 in SeaTumpengan Village, Pineleng District, Minahasa Regency in the study of public administration science.The type of research used in this study is a qualitative approach with descriptive analysis. The selection ofa qualitative approach to answer the research problem proposed by emphasizing on interpretation, not ongeneralization and more on revealing the meaning and understanding of the phenomenon ofimplementing the policy for handling Covid 19 in Sea Tumpengan Village, Pineleng District, MinahasaRegency . Data collection techniques used include documentation, observation and interviews. Qualitativedata analysis techniques used in this study refer to the analysis techniques proposed by Miles andHuberman, namely data reduction, data presentation, drawing conclusions or verification. It can beconcluded that the implementation of the Covid-19 handling policy in Sea Tumpengan Village, PinelengDistrict, Minahasa Regency is seen from the environmental conditions, the relationship betweenorganizations, the budget that comes from village funds and the facilities used by the implementing teamand direct assistance by the community to meet the needs of the implementing team make theimplementation of the policy to handle Covid 19 run well.Kata Kunci : Implementation, Policy, Handling, Covid-19